2000
DOI: 10.1111/j.1574-6941.2000.tb00698.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of 3-chlorobenzoate degrading aerobic bacteria isolated under various environmental conditions

Abstract: The rates of bacterial growth in nature are often restricted by low concentrations of oxygen or carbon substrates. In the present study the metabolic properties of 24 isolates that had been isolated using various concentrations of 3-chlorobenzoate, benzoate and oxygen as well as using continuous culture at high and low growth rates were determined to investigate the effects of these parameters on the metabolism of monoaromatic compounds. Bacteria were enriched from different sampling sites and subsequently iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Metabolism of aromatics via gentisate has been studied less extensively than metabolism via catechol, and it is not clear whether one pathway has an advantage over the other. A study investigating bacteria that metabolize 3-chlorobenzoate suggested that micro-organisms using the gentisate pathway have lower maximum specific growth rates and lower apparent half-saturation constants for oxygen and 3-chlorobenzoate; thus, they may be well adapted to substrate-and/or oxygen-limited conditions (Krooneman et al, 2000). If these same characteristics are applicable to strain CJ2, they could help explain why it is successful in naphthalene-contaminated sediments despite being sensitive to inhibitory effects of naphthalene.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolism of aromatics via gentisate has been studied less extensively than metabolism via catechol, and it is not clear whether one pathway has an advantage over the other. A study investigating bacteria that metabolize 3-chlorobenzoate suggested that micro-organisms using the gentisate pathway have lower maximum specific growth rates and lower apparent half-saturation constants for oxygen and 3-chlorobenzoate; thus, they may be well adapted to substrate-and/or oxygen-limited conditions (Krooneman et al, 2000). If these same characteristics are applicable to strain CJ2, they could help explain why it is successful in naphthalene-contaminated sediments despite being sensitive to inhibitory effects of naphthalene.…”
Section: Discussionmentioning
confidence: 99%
“…The benA PCR-DGGE was not designed for monitoring such a degrader (gp-type bacteria). Krooneman et al pointed out the possibility that gp-type bacteria play an important role in the degradation of 3CB, especially under conditions of low oxygen and low substrate concentrations 17) . So far as the present study is concerned, however, we thought that any contribution of gp-type bacteria to the degradation would be small, because the soil was aerobic and the concentration of 3CB was relatively high.…”
Section: Discussionmentioning
confidence: 99%
“…6, No. 3;2014 Figure 5. The effect of adaptation on 3,4-DCBA biodegradation on the bacterial cells (C. jeikeium).…”
Section: Effect Of Substrate Adaptation On Biodegradation Of 34-dcbamentioning
confidence: 99%
“…A huge number of bacterial and fungal genera possess the ability to degrade organic pollutants and these microorganisms are of particular relevance for the biodegradation of such compounds and are exemplarily described with reference to the degradation of aliphatic and aromatic hydrocarbons as well as their chlorinated derivatives. The most rapid and complete degradation of the majority of pollutants is brought about under aerobic conditions (Krooneman et al, 2000). The first dechlorination step of 3,4-DCB is catalyzed by the 4-CB dehalogenase, while a soluble dehalogenase was responsible for dechlorination of 3-C-4-OHB.…”
Section: Introductionmentioning
confidence: 99%